The Role of Madrasah Heads in Improving Teacher Pedagogical Skills at Darul Mursyid Private MA, South Tapanuli Regency - Mardianto, Mardianto; Syaukani, Syaukani; Harahap, Anwar Soleh (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2022)
The head of the madrasa is the driving force that determines the basic goals of the madrasa, determines how the objectives of the madrasa and education as a whole are achieved, including increasing the feasibility of teaching staff. play an important role in passing the quality of education. As stated in Article 14 (1) PP 30 of 2005, “Madrasah management is responsible for organizing educational activities, managing madrasas, fostering other education personnel and their utilization. Therefore, the Head of Madrasah needs to provide a special strategy in improving the competence of his educators (teachers). This study uses a qualitative approach by using data collection methods in the form of observation, interview, and recording. The data analysis technique used descriptive qualitative data analysis. In this study, the examiner uses three triangles, namely the root triangle, the method, and the reviewer triangle. Triangulate sources by comparing reviews, interviews and documents. Triangulation is done by collecting cyclical data such as methodological observations, interviews, and documents. The triangle reviewer compares the informant with the data obtained from other informants. The results of this study are as follows.1. Therefore, the Head of Madrasah needs to provide a special strategy in improving the competence of his educators (teachers). (a. Involvement of teachers in education; (b) To enable teachers to improve their knowledge and skills by studying at higher educational levels (c) Efforts to build an assessment team of learning outcomes; (d) Use of memorable learning periods (e) (f) ) Provide counselors and teachers about advances in science and technology, (g) provide examples of good teaching and counseling practices 2)). Darul Mursid, Personal Bachelor of South Tapanuri Regency, supports the leadership element2). Supporting Factors for Madrasah Heads as Innovators in Improving Teacher Pedagogical Competence at Darul Mursyid Private MA, South Tapanuli Regency, namely: (a). Head of professional madrasa, (b). Higher educator motivation, and (c). Student learning motivation is high. 3). The inhibiting factors for the efforts of the Madrasah Head as an Innovator for Improving Teacher Pedagogical Competence at the Darul Mursyid Private MA, South Tapanuli Regency, are: (a). Insufficient infrastructure, (b). Internet connection is not good.